(untitled) (Agricultural Engineering, 2017)
The objective of the research was to determine the impact of the friction force between the cylinder wall and soil on the soil compaction resistance in relation to the sample height and diameter of the compaction plate. Samples with the diameter of (D) 100 mm and heights (H) of 30, 50 or 100 mm made of of soil material collected from subsoil of the selected plastic soils were used. The soil material wasidentified by the following properties: the granulation type, density of the solid phase, humus and calcium carbonate content, reaction, plastic and liquid limit. Properties of the samples were described with moisture, dry density of solid particles, porosity of aeration, plastic degree and saturation. The samples were loaded with plates of varied diameters (dA: 20; 30; 50; 70; 80; 90 and 98 mm) measuring at the same time forces on the main plate (FA) and the bottom one (FB) with the fixed diameter (dB=98 mm). The registered relationships between the forces FA and FB and plate sinkage (samples deformation) were used for determination of the impact of external friction forces (between the cylinder wall and soil) on the compression resistance of soils. It was found out that the participation of the friction force in relation to the height of samples and plate diameter varied from 0 to ca. 70%. It was proved that one may avoid the impact of the plate diameter dA on the measurement of force FA, when the relation dA/D, for samples with the heights of H30 and H50, is respectively within 0.5 ≤ dA/D < 0.8 and 0.5 ≤ dA/D < 0.7.